2015
DOI: 10.7150/ijms.12262
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Systemic Arterial Compliance is Associated with the Severity of Heart Failure Symptoms in Moderate-to-Severe Aortic Stenosis: a Cross-Sectional Retrospective Study

Abstract: Background: Patients with aortic stenosis (AS) may develop heart failure even in the absence of severe valve stenosis. Our aim was to assess the contribution of systemic arterial properties and the global left ventricular afterload to graded heart failure symptoms in AS.Methods: We retrospectively reviewed medical records of 157 consecutive subjects (mean age, 71±10 years; 79 women and 78 men) hospitalized owing to moderate-to-severe degenerative AS. Exclusion criteria included more than mild aortic insufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…It may also represent an indirect measure of afterload and has been found to be reduced in patients with poorly controlled systolic hypertension . Patients with reduced SAC were found to have poorer prognosis in the context of severe AS, with more severe LV dysfunction . We found that despite normal LVEF, SAC was reduced in patients who switched from normal‐flow to low‐flow AS and conversely increased in patients who switched from low‐flow to normal‐flow AS.…”
Section: Discussionmentioning
confidence: 99%
“…It may also represent an indirect measure of afterload and has been found to be reduced in patients with poorly controlled systolic hypertension . Patients with reduced SAC were found to have poorer prognosis in the context of severe AS, with more severe LV dysfunction . We found that despite normal LVEF, SAC was reduced in patients who switched from normal‐flow to low‐flow AS and conversely increased in patients who switched from low‐flow to normal‐flow AS.…”
Section: Discussionmentioning
confidence: 99%
“…24 SAC has also been associated with the severity of HF symptoms in moderate to severe AS. 25 Zva can estimate global LV hemodynamic load as the sum of valvular and arterial loads. It has been recently reported that Zva was associated with syncope in AS patients with preserved EF.…”
Section: Discussionmentioning
confidence: 99%
“…The disease predominantly affects children and often presents with stroke or recurrent transient ischemic attacks that are commonly accompanied by paralysis affecting one side of the body, muscle weakness, and seizures [8]. Medical management may involve drugs such as antiplatelet agents which are generally given to prevent thrombosis, but the mainstay of treatment remains surgery [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Many surgical procedures have been described to restore blood flow, among them two are mostly discussed in literature; first is known as the indirect procedure, including encephaloduroarteriosynangiosis (EDAS), while the second is the direct method which includes superficial temporal artery and middle cerebral artery (STA-MCA) bypass. Combined approaches including both direct and indirect methods have shown good results and are of prime significance [9]. …”
Section: Discussionmentioning
confidence: 99%